The effects of economic sanctions on trade: New evidence from a panel PPML gravity approach - Jonas Frank (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2018)
Economic sanctions are a popular diplomatic tool for countries to enforce political demands abroad or to punish non-complying countries. There is an ongoing debate in the literature about whether this tool is effective in reaching these goals. This paper looks at the consequences of sanctions for bilateral trade values between 1987 and 2005. In order to quantify the direct effects of sanctions on the trade flows between countries I use PPML as well as several other econometric specifications to estimate the gravity equation with country pair, sender-time, and target-time fixed effects. Following Heid et al. (2015) I include intra-national as well as international trade flows, to reduce the endogeneity bias of trade policy instruments. The estimates reveal that there is a significant decrease in the value of trade after the introduction of sanctions, which turns out to be driven by moderate sanctions. I also check whether countries that are affected by sanctions switch to other trade partners, but here is no robust evidence for behavior like this.
urn:nbn:de:bsz:100-opus-15056
Keywords: F13; F14; 330; Economic Sanctions; International Trade; Panel Gravity Model; PPML